2014
DOI: 10.1111/exsy.12079
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model for business process event and outcome prediction

Abstract: Large service companies run complex customer service processes to provide communication services to their customers. The flawless execution of these processes is essential because customer service is an important differentiator. They must also be able to predict if processes will complete successfully or run into exceptions in order to intervene at the right time, preempt problems and maintain customer service. Business process data are sequential in nature and can be very diverse. Thus, there is a need for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Process mining techniques focus on extracting knowledge from the event data [4]. Considering the complexity and level of divergence in the real-world business environment, process mining has emerged as a solution of several process analytic techniques [6], such as process discovery to explore the process data through modelling and analysing the behaviour of events in the log [7], monitor the process to analyse the conformance of the extracted process data with the models generated as a result of the process discovery and enhance the quality of original process through extracted knowledge [8]. In 2015, Hompes et al proposed a generic framework for process discovery based on Markov Cluster algorithm [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Process mining techniques focus on extracting knowledge from the event data [4]. Considering the complexity and level of divergence in the real-world business environment, process mining has emerged as a solution of several process analytic techniques [6], such as process discovery to explore the process data through modelling and analysing the behaviour of events in the log [7], monitor the process to analyse the conformance of the extracted process data with the models generated as a result of the process discovery and enhance the quality of original process through extracted knowledge [8]. In 2015, Hompes et al proposed a generic framework for process discovery based on Markov Cluster algorithm [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Once done, further exploration of the log is more straightforward and can follow traditional process mining steps [5]. Things become more complicated when the process operates in an established real-world business environment and adjustments towards achieving business goals tend to change the process regularly [6]. This change is normally brought about by human intervention and is mostly for specific cases, for example, changing the pre-requisites of a course for specific students in an academic environment, or allow students to apply for medical leave through an online portal where the process normally expects a hard copy of the doctor's prescription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data mining and machine learning techniques have been applied in various application domains for knowledge discovery and business intelligence (Gupta, Ahuja, Malhotra, Bala, & Kaur, 2017;Kim et al, 2017;Le, Gabrys, & Nauck, 2017;Lee et al, 2017;Márquez-Vera et al, 2016;Moro, Cortez, & Rita, 2018). Machine learning techniques have also been compared for customer churn prediction (Vafeiadis, Diamantaras, Sarigiannidis, & Chatzisavvas, 2015).…”
Section: Customer Churn Predictionmentioning
confidence: 99%
“…Experiments were conducted on records of processes obtained from a telecommunication company. An approach by Le et al (2017) uses sequential k-nearest neighbor classification and an extension of Markov models to predict the next process steps by considering temporal features. Using the same process log data as Le et al (2014), they showed the superiority of this model over Markov and Hidden Markov Models (HMM).…”
Section: Related Workmentioning
confidence: 99%